2016
DOI: 10.1111/sjop.12306
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of positive and negative metacognitive beliefs in depression

Abstract: Many psychological models have been developed to explain the development and maintenance of depression. The most widely evaluated model is the cognitive model of depression, and it is against this model that emerging models should be compared. Accordingly, this cross-sectional study examined whether metacognitive beliefs, as specified in the metacognitive model of depression, would explain additional variance in depressive symptoms over dysfunctional attitudes; the core feature of the cognitive model. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…Second, PB constitute an important part of the metacognitive model of depression (Wells et al., ; Yilmaz, Gençöz, & Wells, ). PB have been assumed to play an important role in the onset of depression as a link between rumination and depression (Huntley & Fisher, ; Weber & Exner, ). In our study, however, neither initial status nor change in PB emerged as significant predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, PB constitute an important part of the metacognitive model of depression (Wells et al., ; Yilmaz, Gençöz, & Wells, ). PB have been assumed to play an important role in the onset of depression as a link between rumination and depression (Huntley & Fisher, ; Weber & Exner, ). In our study, however, neither initial status nor change in PB emerged as significant predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Positive metacognitive beliefs about worry and rumination (PB, e.g., "Worrying helps me to avoid problems in the future"), negative metacognitive beliefs about the uncontrollability of rumination (NB, e.g., "My worrying is dangerous for me"), and metacognitive beliefs concerning the need to control one's thoughts (NFC, e.g., "If I did not control a worrying thought, and then it happens, it would be my fault") seem to play a particular role in depression (Ruiz & Odriozola-Gonzalez, 2015). Cross-sectional studies showed significant associations between metacognitive beliefs, depressive symptoms, and rumination (Halvorsen et al, 2015;Huntley & Fisher, 2016;Papageorgiou & Wells, 2001;Roelofs et al, 2007;Solem, Hagen, Hoksnes, & Hjemdal, 2016). However, cross-sectional studies are clearly not appropriate for establishing causal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In line with such theorizing, higher levels of depressive symptomatology are associated with less favorable attitudes toward help‐seeking (Keeler, Siegel, & Alvaro, ) and lower confidence that help‐seeking will lead to positive outcomes (Siegel et al, ). Although there are some exceptions (e.g., Chin, Chan, Lam, Lam, & Wan, ), research typically indicates a relationship between heightened depressive symptomatology and less favorable help‐seeking attitudes among children and adolescents (Garland & Zigler, ), college students (Huntley & Fisher, ), and adults (Lienemann & Siegel, ). Research has also identified this relationship across cultures (e.g., Chinese undergraduates, Wang, Peng, Li, & Peng, ; Spanish‐Dominant Hispanics, Keeler & Siegel, ).…”
Section: Attitude Changementioning
confidence: 99%
“…Moreover, rumination among people with depression has been described as intrusive, persistent, and difficult to suppress (Andrews & Thomson, ; Orth, Robins, & Roberts, ). In addition to increased levels of rumination, heightened depressive symptomatology is associated with favorable beliefs about rumination (e.g., agreement with items such as, “In order to understand my feelings of depression, I need to ruminate about my problems”; Huntley & Fisher, ). As such, it is likely that people with depression hold highly elaborated attitudes about the future likelihood of happiness and their attitudes toward help‐seeking—making these attitudes more resistant to persuasive attempts as depressive symptomatology increases.…”
Section: Attitude Changementioning
confidence: 99%
“…Studies show a strong association between depressive symptoms and cognitive fusion (e.g., Cvetanovski 2014; Dinis et al 2015;Gillanders et al 2014), decentering (e.g., Bieling et al 2012; COGNITIVE FUSION'S PREDICTIVE POWER OF DEPRESSIVE SYMPTOMS 4 2007a; Fresco et al 2007b;Linares et al 2016;Mori and Tanno 2015), mindfulness (e.g., Baer et al 2008;Brown and Ryan 2003;Carmody and Baer 2008), and metacognitive dimensions (e.g., Huntley and Fisher 2016;Lashkary et al 2016;Sarisoy et al 2014). …”
Section: Concurrent Effects Of Different Psychological Processes In Tmentioning
confidence: 99%